Effect of antimicrobial activities on the various solvents extracts of leaves of Scurrula ferruginea (Jack) Danser (Loranthaceae) - Justine, Vanielie Terrence; Mustafa, Muskhazli; Go, Rusea (Universiti Putra Malaysia Press, 2018)
Scurrula ferruginea is widely distributed in Southeast Asian countries and has commonly been used as a medicinal plant to treat many diseases caused by microbes. This study was conducted to evaluate the effect of using various solvents extractions on S. ferruginea leaves and their antimicrobial activities. Oven dried (60°C) leaves of S. ferruginea were extracted with aqueous and organic solvents. Antimicrobial activities of the extracts were tested against Staphylococcus aureus S261, Escherichia coli E57, Candida albicans C205 and Trichophyton rubrum T62 using Disc Diffusion Method, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC) respectively. The ideal solvent was 80% methanol with values of the zone of inhibition ranging from 7.98 to 9.71 mm and 450 to 900μg/mL (MIC and MBC) for S. aureus and E. coli, respectively. The present findings revealed that the leaves of S. ferruginea have inhibitory effects on several pathogenic microbes and can be suggested as a potential source of natural antimicrobial compounds.